Dexamethasone Intravitreal Implant for Idiopathic Retinal Vasculitis, Aneurysms, and Neuroretinitis. Issue 5 (September 2013) - Empeslidis, Theodoros; Banerjee, Somnath; Vardarinos, Athanasios; Konstas, Anastasios G.P.
Purpose: To present the short-term favorable clinical results with the dexamethasone intravitreal implant in a patient with florid idiopathic retinal vasculitis, aneurysms, and neuroretinitis syndrome (IRVAN) . Methods: A 26-year-old man presented with significant bilateral deterioration of vision due to vitreous hemorrhage and neuroretinitis with a background of vasculitis and neovascularization. The patient was initially treated with high doses of oral steroids (80 mg prednisolone), which were gradually tapered, and also received extensive argon laser photocoagulation in ischemic areas in both eyes. Despite vigorous treatment and an initial positive response to treatment, pars plana vitrectomy was eventually needed to address the recurrent vitreous hemorrhages in the left eye. Consequently, visual acuity improved from 0.1 to 0.2 (Snellen) and there was no relapse of vitreous hemorrhage. Persistent macular edema was noted, however, and it was decided to treat with a dexamethasone 0.7 mg intravitreal implant . Results: Following the dexamethasone implant OS, visual acuity improved significantly from 0.2 to 0.5 (Snellen), the patient reported much less distortion, and there was marked reduction in central retinal thickness from 467 to 234 microns. The patient remains in remission without any exudation in the macula at 4 months follow-up . Conclusions: Dexamethasone 0.7 mg intravitreal implant appears to be a safe and effective solution in the treatment of macular edema in patients with IRVAN syndrome and could possibly be a treatment option for other cases of inflammatory induced macular edema .